Независимо используемый дательный падеж в литовском, русском и словенском языках: некоторые замечания к сопоставительному анализу - Коницкая, Елена (Vilnius University Open Series, 2021)
The present article examines independent or non-subcategorized uses of the dative case in three languages: Lithuanian, Russian, and Slovenian. The analysis is based on the classification of the dative functions proposed in the literature on Lithuanian (Holvoet & Čižik-Prokaševa 2005; Rembiałkowska 2007): 1) dativus ethicus, 2) dativus iudicantis; 3) dativus sympatethicus; 4) dativus commodi. The comparative methodology is based on establishing similarities and differences between the examples in each group identified in Lithuanian and their Slavic counterparts. The analysis shows that the first group is represented in all three languages, while in the other three groups considerable differences are observed. In some cases, in the second group, the Lithuanian non-subcategorized dative corresponds to the Russian construction для (‘for’) + GEN, and to the Slovenian construction za (‘for’) + ACC. In the third and fourth groups, the Lithuanian dative case, which usually represents an external possessor, often corresponds to the Slovenian dative, differing nonetheless from Russian where the construction y (‘at’) + GEN is used.
Keywords: non-subcategorized dative; external possession; Lithuanian; Russian; Slovenian